Oxford A-Z of English usage - Butterfield, Jeremy( 1951-) (Oxford: Oxford University Press, 2013)
This handy guide provides crystal-clear help with writing correctly and appropriately in everyday situations. Arranged alphabetically, the book contains concise entries with guidance on individual words and phrases, and longer entries on broader topics such as overused words, bullet points, and avoiding sexist language.
Keywords: English language